STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU - Riana Adriyani; Syarwani Ahmad; Nurlina Nurlina (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
This study aims to describe and analyze the principal’s strategies in improving teacher professionalism, focusing on pedagogical and professional competencies at SMP Negeri 4 Rambutan. The study employs a descriptive qualitative approach with a total of 11 informants, consisting of 1 principal, 2 vice principals, and 8 teachers selected purposively. Data collection techniques include in-depth interviews, observations, and documentation, while data analysis uses the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing. The findings indicate that the principal’s strategies are implemented through integrated stages of planning, implementation, and supervision. The improvement in teacher professionalism is primarily reflected in pedagogical competence (classroom management and the use of innovative teaching methods) and professional competence (mastery of subject matter). One innovative strategy applied is the implementation of in-house training based on teacher learning communities to overcome budget constraints. Evaluation is conducted through academic supervision, routine meetings, and continuous teacher performance appraisal (PKG). Overall, the principal has successfully established a collaborative, adaptive, and quality-oriented school culture aimed at improving the teaching and learning process. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis strategi kepala sekolah dalam meningkatkan profesionalisme guru yang mencakup aspek kompetensi pedagogik dan profesional di SMP Negeri 4 Rambutan. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan jumlah informan sebanyak 1 kepala sekolah, 2 wakil kepala sekolah, dan 8 guru yang dipilih secara purposive. Teknik pengumpulan data dilakukan melalui wawancara mendalam, observasi, dan dokumentasi, sedangkan analisis data menggunakan model interaktif Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa strategi kepala sekolah dilaksanakan melalui tahapan perencanaan, pelaksanaan, dan pengawasan yang terintegrasi. Peningkatan profesionalisme guru terlihat terutama pada aspek kompetensi pedagogik (pengelolaan kelas dan penggunaan metode pembelajaran inovatif) serta kompetensi profesional (penguasaan materi ajar). Salah satu strategi inovatif yang diterapkan adalah pelaksanaan in-house training berbasis komunitas belajar guru untuk mengatasi keterbatasan anggaran. Evaluasi dilakukan melalui supervisi akademik, rapat rutin, serta penilaian kinerja guru (PKG) secara berkelanjutan. Secara keseluruhan, kepala sekolah berhasil menciptakan budaya sekolah yang kolaboratif, adaptif, dan berorientasi pada peningkatan mutu pembelajaran.